New and exploratory therapeutic agents for asthma - Yeadon, Michael; Diamant, Zuzana (Lung biology in health and disease, 2000)
This work addresses treatment strategies for asthma, focusing on the genetics and molecular biology of asthma and pointing the way toward new, commercially viable therapies. It also presents information on the epidemiology, pathology, pharmacology and pulmonology of asthma.